Interaction of Natural Dietary and Herbal Anionic Compounds and Flavonoids with Human Organic Anion Transporters 1 (SLC22A6), 3 (SLC22A8), and 4 (SLC22A11). (21st March 2013) - Wang, Li; Sweet, Douglas H.
Abstract : Active components of complementary/alternative medicines and natural supplements are often anionic compounds and flavonoids. As such, organic anion transporters (OATs) may play a key role in their pharmacokinetic and pharmacological profiles, and represent sites for adverse drug-drug interactions. Therefore, we assessed the inhibitory effects of nine natural products, including flavonoids (catechin and epicatechin), chlorogenic acids (1, 3- and 1, 5-dicaffeoylquinic acid), phenolic acids (ginkgolic acids (13 : 0), (15 : 1), and (17 : 1)), and the organic acids ursolic acid and 18 β -glycyrrhetinic acid, on the transport activity of the human OATs, hOAT1 (SLC22A6), hOAT3 (SLC22A8), and hOAT4 (SLC22A11). Four compounds, 1, 3- and 1, 5-dicaffeoylquinic acid, ginkgolic acid (17 : 1), and 18 β -glycyrrhetinic acid, significantly inhibited hOAT1-mediated transport (50 μ M inhibitor versus 1 μ M substrate). Five compounds, 1, 3- and 1, 5-dicaffeoylquinic acid, ginkgolic acids (15 : 1) and (17 : 1), and epicatechin, significantly inhibited hOAT3 transport under similar conditions. Only catechin inhibited hOAT4. Dose-dependency studies were conducted for 1, 3-dicaffeoylquinic acid and 18 β -glycyrrhetinic acid on hOAT1, and IC50 values were estimated as 1.2 ± 0.4 μ M and 2.7 ± 0.2 μ M, respectively. These data suggest that 1, 3-dicaffeoylquinic acid and 18 β -glycyrrhetinic acid may cause significant hOAT1-mediated DDIs in vivo ; potential should be considered for safety issues during use and in future drug development.